Thymic cancer in lynch syndrome: an unusual association. Issue 4 (8th April 2020) - Pandey, Deepali; Shepro, David Scott
Abstract : Lynch syndrome has been associated with predominantly colorectal, endometrial, and ovarian cancer. We report hereby an unusual case of thymic carcinoma in a patient with Lynch syndrome. A 45-year-old Caucasian woman with a personal history of Lynch syndrome (MLH1 heterozygous mutation) presented with dyspnea, chest pain, and dysphagia. CT chest showed a bulky anterior mediastinal mass, pulmonary nodules, and pericardial effusion. Lung biopsy demonstrated a poorly differentiated carcinoma with squamous features with extensive necrosis, favouring thymic origin. Genomic studies on the tumour revealed deficient mismatch repair status with a two-copy deletion of MLH1 at 3p22.2 and c-Kit mutation. She received carboplatin and paclitaxel, with initial clinical improvement, but then died within 3 months after diagnosis. This case highlights that thymic cancer may be one of the malignancies associated with Lynch syndrome, and MLH1 gene mutation may have a role in the pathogenesis of thymic cancer.